A length-independent index for timber bow and spring validated on Eucalyptus grandis. Issue 1 (2nd January 2023) - Balboni, Bruno Monteiro; Wessels, C. Brand; Garcia, José Nivaldo
ABSTRACT: Warping is a frequently encountered defect in wood products which is evaluated in different ways by various sawn timber product standards. However, there are weaknesses in the current evaluation methods especially when comparing warp in different board lengths. The objective of the work described in this paper was to develop a theoretical model of bow and spring based on pure bending theory and to evaluate the model experimentally. A warp index was developed that allows comparison of bow and spring in timber boards independent of the length. The theoretical model was evaluated in experimental trials with Eucalyptus grandis of board warping caused by growth stress release as well as board warping caused by differences in longitudinal shrinkage after drying. The model explained the warping phenomenon well and the errors between theoretical and observed data were, on average, very small. The warp index developed allows assessment of bow and spring in any length, and might be useful with segregating portions of lower distortions for modern production systems of finger-jointed lamellas for engineered wood products, as well as for assessing growth stress levels, sawmilling processes and timber seasoning techniques.